Ergonomía del mobiliario de aula y su impacto en la salud postural de los estudiantes de la Facultad de Agronomía. Loreto 2024 - Guedez Garces, Erick Jesus Gabriel (2025)
At the Faculty of Agronomy in Loreto, there is a lack of evidence on how classroom furniture affects postural health, despite international and national reports of anthropometric mismatches and a high prevalence of musculoskeletal complaints. This study analyzes furniture ergonomics and its impact on students during 2024. It draws on literature documenting inadequate furniture and on INACAL’s Peruvian Technical Standards (NTP) that set design and safety requirements. Using a quantitative, non-experimental, cross-sectional, descriptive-correlational approach, a random sample of 265 students was surveyed and descriptive analyses, ANOVA, and MANOVA were applied. Findings show that 63.8% remain seated for more than 3 hours, 67.9% adopt inadequate postures, seat height (62.6%) and width (67.2%) are perceived as uncomfortable, and 78.9% report fatigue. MANOVA evidenced a significant effect of furniture width (p<0.001), and ANOVA associated width with lower-back and knee pain. It is concluded that furniture should be redesigned according to student anthropometry and NTP guidelines, prioritizing adjustable width and lumbar support to reduce fatigue and musculoskeletal risks and optimize learning.